Pest categorisation of Ips sexdentatus. (3rd November 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Candresse, Thierry; Chatzivassiliou, Elisavet; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of the six‐toothed bark beetle, Ips sexdentatus (Börner) (Coleoptera: Curculionidae, Scolytinae), for the EU. I. sexdentatus is a well‐defined and distinguishable species, native to Eurasia and recognised mainly as a pest of pine ( Pinus spp., in the pest's whole range) and spruce (mainly Picea orientalis in Turkey and Georgia). It also might occasionally attack Larix spp. and Abies spp. It is distributed throughout the EU (24 Member States). It is a protected zone quarantine pest in Ireland, Cyprus and the United Kingdom (Northern Ireland, Isle of Man), listed in Annex IIB of Council Directive 2000/29/EC. Wood, wood products, bark and wood packaging material are considered as pathways for this pest, which is also able to disperse by flight over tens of kilometres. The adults normally establish on fallen or weakened trees (e.g. after a fire or a drought) and can also mass‐attack healthy trees. The males produce aggregation pheromones that attract conspecifics of both sexes. The insects also inoculate pathogenic fungi to their hosts. There are one to five generations per year. The wide current geographical range of I. sexdentatus suggests that it is able to establish anywhere in the EU where its hosts are present. Sanitary thinning or clear‐felling are the major control methods. Pheromone mass‐trapping is also locally implemented. Quarantine measures are implemented to prevent entry into the protected zones. All criteria for consideration as potential protected zone quarantine pest are met. The criteria for considering I. sexdentatus as a potential regulated non‐quarantine pest are not met since plants for planting are not viewed as a pathway.